Didáctica de la programación lineal con el método gráfico - León Parada, Fernando (Revista Científica, 2007)
Every Linear Programming model has a Objective Function determined by the coefficients of the decision variables. The Objective Function can be represented as a line evaluated on an optimal point which slope depends from the variation of the coefficients. The segments adjacent to the optimal point in the Feasible Region can also determine the variation of this slope. Finally a geometric analysis allows to establishing the constraining of the boundary for the Feasible Region keeping as a domain for the Objective Function.